2022
DOI: 10.1007/s40865-022-00204-z
|View full text |Cite
|
Sign up to set email alerts
|

From Childhood System Contact to Adult Criminal Conviction: Investigating Intersectional Inequalities using Queensland Administrative Data

Abstract: It is well known that youth justice contact is associated with criminal conviction in adulthood. What is less well understood is whether ‘cross-over’ children, who have contact with both child welfare and youth justice systems, experience relatively worse outcomes and, if so, whether these outcomes vary by important demographic factors, such as sex and race. Criminal careers scholars have examined patterns of adult convictions for different groups, but attempts to understand intersectional variation in these o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Although a few previous studies have identified five offending trajectory groups for males and females combined (Broidy et al, 2015; Matthews et al, 2022), our study took a novel approach and identified five separate trajectory groups for females and males, which allowed us to gain a more comprehensive understanding of sex-based similarities and differences in offending patterns through early adulthood. The large female sample and wide age range (10 to 30 years of age), derived from the population-based, prospective, longitudinal, linked administrative data set, made it possible to achieve a more comprehensive analysis of how sex and Indigenous status intersect to shape offending trajectories.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a few previous studies have identified five offending trajectory groups for males and females combined (Broidy et al, 2015; Matthews et al, 2022), our study took a novel approach and identified five separate trajectory groups for females and males, which allowed us to gain a more comprehensive understanding of sex-based similarities and differences in offending patterns through early adulthood. The large female sample and wide age range (10 to 30 years of age), derived from the population-based, prospective, longitudinal, linked administrative data set, made it possible to achieve a more comprehensive analysis of how sex and Indigenous status intersect to shape offending trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to exploring how sex is related to offending trajectories, some have also considered the important role of race/ethnicity and how sex and race/ethnicity intersect to shape offending trajectories (e.g., Broidy et al, 2015; Doherty & Ensminger, 2014; Matthews et al, 2022; Piquero & Buka, 2002). For example, Piquero and Buka (2002) found that African American females and males were more likely than their non-African American counterparts to populate the chronic/persistent offending trajectory.…”
Section: The Importance Of Considering the Intersection Of Sex And Ra...mentioning
confidence: 99%
See 1 more Smart Citation
“…While young people displaying high frequency or 'chronic' offending behaviour have not traditionally been a target for diversion, they comprise a heterogenous group in terms of the nature of their offending, and expanding appropriate diversionary options for lower harm offences could reduce the long-term entrenchment of these young people in the criminal justice system (McCarthy et al, 2021). Young people engaged in chronic offending have often experienced many adverse and challenging life experiences including child maltreatment, cognitive and learning disabilities, family dysfunction or estrangement, substance use, racial discrimination, and educational exclusion (Evans et al, 2016;Fox et al, 2015;Matthews et al, 2022;McVilly, 2022;Whitten et al, 2019), and thus often have multiple persistent factors contributing to their offending behaviour. There is evidence that diversion programs targeted to high-risk young people can be effective in reducing recidivism, particularly when it includes a skills-building component and is targeted to identified needs (Wilson & Hoge, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There is extensive scholarship on child maltreatment more broadly in Australia. Research has explored many deleterious outcomes of child maltreatment victimisation, such as mental health concerns and criminal offending (Green et al, 2020; Malvaso et al, 2019; Matthews et al, 2022). Other studies have examined factors associated with contact with CPS as a parent, including economic disadvantage, criminal offending, domestic and family violence (DFV) and mental health concerns (Doidge et al, 2017; Gilbert et al, 2020; Whitten et al, 2021).…”
Section: Strengths and Limitations Of The Existing Evidence Basementioning
confidence: 99%